2004
DOI: 10.1016/j.devcel.2004.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Roles of Cdc42, Par-6, aPKC, and Lgl in the Establishment of Epithelial Polarity during Drosophila Embryogenesis

Abstract: How epithelial cells subdivide their plasma membrane into an apical and a basolateral domain is largely unclear. In Drosophila embryos, epithelial cells are generated from a syncytium during cellularization. We show here that polarity is established shortly after cellularization when Par-6 and the atypical protein kinase C concentrate on the apical side of the newly formed cells. Apical localization of Par-6 requires its interaction with activated Cdc42 and dominant-active or dominant-negative Cdc42 disrupt ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
361
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(379 citation statements)
references
References 62 publications
15
361
2
1
Order By: Relevance
“…When unphosphorylated, apical cell cortex-localized Lgl can interact with and inhibit the enzyme activity of aPKC [15,26]. Upon phosphorylation, Lgl undergoes conformational changes causing its dissociation from the apical cortex and concomitant release of its inhibition on aPKC, and subsequent accumulation at the basal-lateral membranes [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When unphosphorylated, apical cell cortex-localized Lgl can interact with and inhibit the enzyme activity of aPKC [15,26]. Upon phosphorylation, Lgl undergoes conformational changes causing its dissociation from the apical cortex and concomitant release of its inhibition on aPKC, and subsequent accumulation at the basal-lateral membranes [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo imaging data have demonstrated that Dlg, Lgl and Scribble interdependently colocalize to the lateral membranes of epithelial cells and thereby specify the lateral membrane domain by excluding apical components from this region [2,6]. However, it is still not clear how Lgl is brought to the lateral membrane, although it is well established that apical atypical protein kinase C (aPKC) activity is required for excluding Lgl from apical membranes [15]. In dlg mutant embryos, Lgl basal membrane association is lost, indicating that Dlg may play a vital role in recruiting Lgl to the basal membranes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, evidence was provided that mammalian Lgl forms complexes with Par6/atypical PKC regulating epithelial cell polarity (Plant et al, 2003;Yamanaka et al, 2003). Upon cell-cell contact-induced cell polarization, Lgl is phosphorylated by atypical protein kinase C (aPKC) resulting in a dissociation of Lgl from Par6/ aPKC followed by an accumulation of Lgl along the basolateral membrane, where it contributes to the formation of the basolateral membrane domain (Tanentzapf and Tepass, 2003;Hutterer et al, 2004) and to correct positioning of epithelial junctions (Borg, 2004). Additionally, recent studies revealed that Lgl has the ability to inhibit notch signaling (Justice et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…First, Cdc42 regulates PAR protein localization and controls the anteriorposterior polarity in Caenorhabditis elegans embryos (17,18). Secondly, Cdc42 sequentially directs Par-6, aPKC, and Lgl to establish the epithelial polarity in Drosophila (19). Thirdly, the mammalian Par-aPKC protein complex interacts with Cdc42 and Rac1 (20).…”
mentioning
confidence: 99%